The Research on Philosophical Foundations of the One Belt and One Road Initiative: Theoretical Background - Jidan Xu (International Society of Philosophy and Cosmology, 2021)
This paper aims to analyse the current theoretical background related to the philosophical foundations of the Belt and Road Initiative, which is represented in current publications. The Belt and Road Initiative is not only an important innovation in China's ideological discourse but also a "new strategy, new project, and new practice" in China's diplomatic strategy and global governance. Philosophy-based analysis framework can effectively clarify its ideological context, value orientation and practical orientation: historically, human emancipation constitutes the value orientation and practical significance of the Belt and Road Initiative; ontologically, the Belt and Road Initiative is a contemporary interpretation and Chinese discourse of the "community of free people," which is of great significance for dispelling the charm of the "false community" and building a "true community." From the axiological point of view, the Belt and Road Initiative takes global justice as its fundamental value pursuit, which transcends Western "liberal cosmopolitanism." It creates principles and rules of justice and the support of justice mechanisms for the "ideal justice philosophy" towards "real justice vision." The philosophies embedded in the Belt and Road Initiative show unity: human liberation is the core theme, and the ultimate pursuit of the Belt and Road Initiative, the community with a shared future for humankind is the structure and path of the Belt and Road Initiative, and global justice is the basic value and practical orientation of the Belt and Road Initiative.